Desain Pit Tambang Air Laya Barat Untuk Memenuhi Target Produksi Tahun 2018 PT. Bukit Asam (Persero) Tbk Sumatera Selatan - Kiki Gusmaningsih; Murad Murad; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2018)
PT. Bukit Asam (Persero), Tbk has produced coal used by various parties, the greater the market demand  for coal use trigger PT. BA to increase target production per year. The target of coal production at Tambang Air Laya Barat in 2017 is 3,500,000 Ton of coal and 20,750,000 BCM overburden. The year 2018 increased to 5,500,000 Ton and 33,000,000 BCM overburden. Based on current conditions the company needs to consider design pit options for the year 2018. Determination target production per month, the number of units that work, as well as the profits to be gained. Result reserve design pit of Tambang Air Laya Barat 2018 obtained 5,639,178 Ton of coal and 32,764,431 BCM overburden with stripping ratio 1:5,81 and recovery 90%. The target production plan is determined based on the capability of the main mining equipment each month. The main fleet allocation for mine for January uses 5 fleets coal and 12 fleets overburden, February 4 fleets coal and 12 fleets overburden, March 4 fleets for coal and 12 fleets for overburden, allocated for April - December equals such as January. Overall cost for coal sales Rp. 7.403.987.221.897,  overburden stripping Rp. 1.285.969.138.002 and  coal  production  Rp. 97.182.467.072, so the profit  to be obtained from mining proceeds for the year 2018  Rp. 6,020,835,616,822, so mining is worth doing feasible. Need to be studied further by considering costs such as coal processing, port transportation, employee salary so that net profit can be obtained.Keywords: Design Pit, Target Production, Overburden, Coal, Profits